Premeditated murder committed in a state of strong emotional excitement: a law enforcement aspect - Starko , Oksana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
One of the main benchmarks in the process of developing and improving measures to prevent premeditated murders committed in a state of strong emotional excitement is the results of the study of judicial practice. In order to find out the typical criminal-law forms of manifestation of these crimes, we analyzed all the verdicts (only 70), approved under Art. 116 of the Criminal Code of Ukraine from October 13, 2010 to December 31, 2024, which were published in the Unified State Register of Judgments. The analysis revealed that the «guilty-victim» relationship had previously committed domestic violence, where the guilty person was a victim and the victim by the abuser. In particular, most of the guilty persons were in family or close relationships with the victim, and the murder was preceded by long-term family conflicts. The overwhelming majority of victims are male persons with alcohol addiction or were intoxicated at the time of murder. The victims were systematically applied to the guilty or other close persons, physical and mental violence. The most common murder tools were those who were at the fault. In particular, every second murder was done by hitting a kitchen knife used mainly by women. The place of committing the crime was the co-housing of the guilty and the victim. Women, unlike men, killed members of their family (80 % of women were family members or close relatives). Men’s victims are other persons, usually unfamiliar before murder (47 %) and family members (53 %).   The study of the verdicts showed that the state of strong emotional excitement of the guilty persons (in every second case was recorded by the physiological affect) was due to systematic physical violence by the victim, and the dominant motive of the murder was the desire to stop physical violence. Thus, the main emphasis in the process of developing measures to prevent premeditated murders committed in a state of strong emotional excitement is counterwork of domestic violence.